The weight of our sky - Hanna Alkaf (Salaam Reads, 2019)
"Amidst the Chinese-Malay conflict in Kuala Lumpur in 1969, sixteen-year-old Melati must overcome prejudice, violence, and her own OCD to find her way back to her mother"--